The localized inflammatory response to bronchoscopic thermal vapor ablation - Gompelmann, Daniela; Eberhardt, Ralf; Ernst, Armin; Hopkins, Peter; Egan, Jim; Stanzel, Franz; Valipour, Arschang; Wagner, Manfred; Witt, Christian; Baker, Kimberly M.; Gotfried, Mark H.; Kesten, Steven; et al. (Respiration, 2013)
Background: Bronchoscopic thermal vapor ablation (BTVA) reduces lung volumes in emphysema patients by inducing a localized inflammatory response (LIR) leading to a healing process of fibrosis, but may also increase symptoms. Objectives: We sought to evaluate whether the clinical manifestation of LIR correlated with patient outcome. Methods: Respiratory adverse events and inflammatory markers were analyzed from a multicenter trial of BTVA in patients with upper-lobe-predominant emphysema. End points including changes in forced expiratory flow (FEV1), lobar volume, St. George's Respiratory Questionnaire (SGRQ), modified Medical Research Council (mMRC) and 6-minute-walk distance (6-MWD) were analyzed according to the presence or absence of a respiratory adverse event requiring treatment with an antibiotic or steroid. Results: Forty-four patients received BTVA. Increases of inflammatory markers were observed with a peak between the second and fourth week. Eighteen respiratory adverse events occurred in 16 patients within 30 days of BTVA, requiring antibiotics and/or steroids. These patients had significantly greater lobar volume reduction (65.3 vs. 33.4%, p = 0.007) and a change in residual volume at 12 months (-933 vs. 13 ml, p < 0.001) associated with a greater improvement of exercise capacity and health-related quality of life than patients without respiratory adverse events. Conclusion: Patients with more prominent respiratory symptoms in the first 30 days following BTVA experience greater efficacy. The clinical manifestations of the LIR are predictive of long-term clinical benefits.
Gesehen am 18.02.2020